Impasses in the wild: Autonomy support in naturalistic, parent-child outdoor play - Baker, Justin; DeLiema, David; Hufnagle, Ashley S.; Carlson, Stephanie M.; Sharratt, Anna; Ridge, Sheila Williams (Frontiers in Education, 2022)
Moments where children encounter problems in their chosen activities represent potentially generative sites for learning, particularly when supportive adults are present to scaffold the learning process. Scholars of autonomy support study these dyadic problem-solving processes in defined tasks, and describe specific types of parental support that have implications for children’s future competence as independent learners. In two exploratory case studies, we expand on the study of autonomy support by examining dyadic problem solving in naturalistic, outdoor family play. We apply a situated method of interaction analysis to perform a detailed, micro-longitudinal decomposition of two extended problem-solving arcs, identifying the specific contributions of parents and children. In doing so, we apply additional lenses of problem-solving, debugging, play-based learning, and intergenerational learning to develop a more comprehensive understanding of endogenous, dyadic problem solving. Our findings suggest the presence of inherent tradeoffs between various potential goals and time horizons for children’s learning and raise actionable considerations for both future research and practice in collaborative learning spaces.